Changes in coagulation in patients with ischemic stroke - Denys Khramtsov; Marina Vikarenko; Galina Kozlova; Yuriy Vorokhta (Journal of Education, Health and Sport, 2017)
The aim of the study was to assess the dynamics of coagulation indices in patients with acute ischemic stroke. The study revealed that atherothrombotic type of stroke prevailed in patients (66.8%), cerebrovascular thrombosis (20.0%) was less common, cardioembolic type was noted in 22.2% of cases. The average inpatient days were 18.11.1. The coagulogram patterns demonstrated hypercoagulation on the 1st  day after stroke onset, on the 3rd  hypercoagulation persisted,. By the seventh day, normalization of mean values of screening parameters of hemostasis was established, and by the 14th day of stroke there was a tendency to hypocoagulation. In patients with hemorrhagic transformation, the values of ICC and ICP parameters increased by day 7, in addition, there was an increase in the content of fibrinogen. A visual display of the blood coagulation activity allows for more accurate selection of anticoagulation therapy, prevention of hemorrhagic transformation.